Human Immunodeficiency Virus Type 1 Vpr Inhibits Axonal Outgrowth through Induction of Mitochondrial Dysfunction - Kitayama, Hiroko (American Society for Microbiology (ASM), 2008)
Human immunodeficiency virus type 1 (HIV-1)-infected macrophages damage mature neurons in the brain, although their effect on neuronal development has not been clarified. In this study, we show that HIV-1-infected macrophages produce factors that impair the development of neuronal precursor cells and that soluble viral protein R (Vpr) is one of the factors that has the ability to suppress axonal growth. Cell biological analysis revealed that extracellularly administered recombinant Vpr (rVpr) clearly accumulated in mitochondria where a Vpr-binding protein adenine nucleotide translocator localizes and also decreased the mitochondrial membrane potential, which led to ATP synthesis. The depletion of ATP synthesis reduced the transportation of mitochondria within neurites. This mitochondrial dysfunction inhibited axonal growth even when the frequency of apoptosis was not significant. We also found that point mutations of arginine (R) residues to alanine (A) residues at positions 73, 77, and 80 rendered rVpr incapable of causing mitochondrial membrane depolarization and axonal growth inhibition. Moreover, the Vpr-induced inhibition was suppressed after treatment with a ubiquinone analogue (ubiquinone-10). Our results suggest that soluble Vpr is a major viral factor that causes a disturbance in neuronal development through the induction of mitochondrial dysfunction. Since ubiquinone-10 protects the neuronal plasticity in vitro, it may be a therapeutic agent that can offer defense against HIV-1-associated neurological disease.